Of counter spaces of provisioning: Reframing the sidewalk as a parasite heterotopia. (June 2018) - Roux, Dominique; Guillard, Valérie; Blanchet, Vivien
This article considers the concept of heterotopia in the context of public space. Based on the observations and interviews with 19 disposers and/or gleaners operating on bulky item collection days, it shows that the sidewalk is (1) a liminal space for unwanted objects that are in transition between disposal and destruction or reappropriation; (2) a regularly practiced space, the meaning of which is redefined by disposers (for depositing) and gleaners (for provisioning); (3) a place of illusion that mirrors the profusion of goods produced by the linear economy; and (4) a space of compensation for the pitfalls of the consumer society. These findings provide a theoretical basis for the new concept of parasite heterotopia, a term that refers to a space that is appropriated by a tactical use of a regulated place, which both reflects and contests a dominant ordering on its own territory. The article adds to previous literature on heterotopias and sustainability by questioning how this "time–space" is involved in the dialectics of capitalism and criticism.